CoS/Nitrogen-doped carbon composites derived from Zeolitic imidazolate frameworks-67 as advanced electrodes for supercapacitors. (June 2022) - Wang, Xianchao; Li, Weirong; Xue, Yanqin; Liu, Junnan; Yue, Yipeng; Zhou, Chunliang; Zhu, Kai; Cao, Dianxue; Chen, Ye; Wang, Guiling
Highlights: CoS/Nitrogen-doped carbon composites prepared by using Zeolitic imidazolate frameworks-67 as precursor shows excellent performance as electrode of supercapacitors. Different synthesis temperatures shows how the structure and performance evolves of CoS/Nitrogen-doped carbon composites as change of temperature. The CoS/Nitrogen-doped carbon composites is a hollow cage-like polyhedron structure formed by the combination of CoS nanosheets and nitrogen doped carbon skeleton at 700 °C curing temperature. Abstract: Using ZIF-67 as precursor, CoS/Nitrogen-doped carbon (CoS/NC) composites are successfully prepared by applying chemical vapor deposition (CVD) treatment at three different curing temperatures. The results show that the optimal curing temperature is 700 °C, and CoS/NC-700 is a hollow cage-like polyhedron structure formed by the combination of CoS nanosheets and nitrogen doped carbon skeleton. The specific capacitance is 789 F g −1 at 1 A g −1 current density and a rate capacity of 80.2% under a 20 A g −1 of current density. The CoS/NC-700//AC capacitor has the highest energy density of 32.8 Wh kg −1 when the power density is 620.0 W kg −1 and the capacitor remains 89.2% of initial capacitance after 10, 000 charge-discharge cycles at current density of 5 A g −1 .